Tirofiban Saves Ischemic Stroke Patients: A Systematic Review and Meta-Analysis - Hira Arshad (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Acute ischemic stroke (AIS) is a leading cause of morbidity and mortality globally. Standard antiplatelet therapies, while partially effective, do not fully inhibit all pathways of platelet aggregation, leaving patients at risk of recurrent thrombotic events. Tirofiban, a glycoprotein IIb/IIIa receptor inhibitor, has shown promise as an adjunctive treatment in AIS. Methods: A comprehensive search was conducted in PubMed, ClinicalTrials.gov, and Cochrane Library from inception to July 2024, following PRISMA guidelines. Inclusion criteria comprised randomized controlled trials (RCTs) and comparative observational studies where tirofiban was used as an adjunct to standard antiplatelet therapy. Primary outcomes included symptomatic intracranial hemorrhage (sICH) and favorable modified Rankin Scale (mRS) scores at 90 days. Secondary outcomes included National Institute of Health Stroke Scale (NIHSS) scores and all-cause mortality. Data was analyzed using Review Manager v5.4.1, with random-effects models employed for all outcomes. Results: Fifteen studies, comprising 4,457 patients, were included. Tirofiban significantly improved the likelihood of achieving favorable mRS scores (OR 1.65, 95% CI [1.29, 2.11], p= 0.0001), with moderate heterogeneity (I²=57%, p=0.006). Tirofiban also significantly reduced NIHSS scores (MD -2.08, 95% CI [-2.77, -1.39], p<0.00001). There was no significant difference in the incidence of sICH between the tirofiban and control groups. Conclusion: Tirofiban as an adjunct to standard antiplatelet therapy in AIS patients significantly improves functional outcomes and reduces neurological impairment without increasing the risk of sICH. Keywords: Tirofiban, Antiplatelet Therapy, Acute Ischemic Stroke, Stroke, Neurology, Dual antiplatelet therapy